Resolvin E1 Promotes Bone Preservation Under Inflammatory Conditions - El Kholy, Karim; Freire, Marcelo; Chen, Tsute; Van Dyke, Thomas E. (Frontiers in Immunology, 2018)
Abstract Resolvins are endogenous anti-inflammatory lipid mediators derived from omega-3 fatty acids. Resolvin El (RvE1), derived from eicosapentaenoic acid (EPA), modulates osteoclasts and immune cells in periodontal disease models. The direct role of RvE1 in bone remodeling is not well understood. Aim: The objective of this study was to determine the impact of RvE1 on bone remodeling under inflammatory conditions. Our working hypothesis is that RvE1 downregulates bone resorption through direct actions on both osteoblast and osteoclast function in inflammatory osteoclastogenesis. Methods: A TNFα induced local calvarial osteolysis model with or without the systemic administration of Resolvin E1 was used. MicroCT analysis, TRAP staining and immunofluorescence analysis were used to evaluate osteoclastogenesis and NFκB signaling pathway activity. Furthermore, to evaluate if RvE1 directly impacts bone cells and the mechanisms involved, primary calvarial mouse osteoblasts were stimulated with interleukin-6 and interleukin-6 receptor and simultaneously incubated with or without RvE1 (100nM). Expression of receptor activator of NFκB ligand (RANKL) and osteoprotegerin (OPG) was measure by ELISA. RNA sequencing and differential expression analysis was performed to determine signaling pathways impacted by RvE1. Results: The systemic administration of RvE1 reduced calvarial bone resorption as determined by µCT. Histologic analysis of calvaria reveal that osteoclastogenesis was reduced as determined by number and size of osteoclasts in TRAP-stained sections (p<0.05). Immunofluorescence staining of calvarial sections revealed that RvE1 reduced RANKL secretion by 25% (p<0.05). Stimulation of osteoblasts with IL-6 increased RANKL production by 30% changing the RANKL/OPG to favor osteoclast activation and bone resorption that was blocked by 100 nM RvE1. RvE1 decreased the production of RANKL maintaining a RANKL/OPG more favorable for bone formation. RNA sequencing and differential expression analysis revealed that RvE1 significantly down regulates osteoclast differentiation mediated by differential regulation of NFκB and PI3K-AKT pathways. Conclusion: RvE1 reduces inflammatory bone resorption. This action is mediated, at least in part, by direct actions on bone cells promoting a favorable RANKL/OPG ratio. Mediators of resolution in innate immunity also directly regulate bone cell gene expression that is modulated by RvE1 through at least 14 specific genes in this mouse model.